Politics and power in territorial planning: insights from two 'Ecological-Economic Zoning' multi-stakeholder processes in the Brazilian Amazon - Gonzales Tovar, J.; Larson, A.M.; Sarmiento Barletti, J.P.; Barnes, G. (Commonwealth Forestry Association, 2021)
The use of multi-stakeholder forums (MSFs) in territorial planning has gained global popularity. These MSFs aim to bring diverse actors together to collaboratively and equitably develop a plan that assigns optimal land uses to a territory. However, as promoting particular land uses and benefits for some actors often comes at a cost to others, territorial planning MSFs may reproduce or even exacerbate, rather than mitigate, conflicts and asymmetries. We comparatively analyze collaboration, power relations and sustainability goals in the Ecological-Economic Zoning commissions of Acre and Mato Grosso, Brazil, which fall under the same federal mandate but operate in contrasting contexts. We show how territorial planning MSFs have better chances of meeting their goals when they are understood as political processes: in this case, when they emerge from and are nourished by powerful local social-environmental movements and alliances, rather than being technocratic initiatives opposed by powerful local production-business alliances.